Effectiveness of Therapeutic Exercise in Fibromyalgia Syndrome: A Systematic Review and Meta-Analysis of Randomized Clinical Trials. (20th September 2017) - Sosa-Reina, M. Dolores; Nunez-Nagy, Susana; Gallego-Izquierdo, Tomás; Pecos-Martín, Daniel; Monserrat, Jorge; Álvarez-Mon, Melchor
Abstract : Objective . The aim of this study was to summarize evidence on the effectiveness of therapeutic exercise in Fibromyalgia Syndrome. Design . Studies retrieved from the Cochrane Plus, PEDro, and Pubmed databases were systematically reviewed. Randomized controlled trials and meta-analyses involving adults with fibromyalgia were included. The primary outcomes considered in this systematic review were pain, global well-being, symptoms of depression, and health-related quality of life. Results . Effects were summarized using standardized mean differences with 95% confidence intervals using a random effects model. This study provides strong evidence that physical exercise reduces pain (−1.11 [95% CI] −1.52; −0.71; overall effect p < 0.001 ), global well-being (−0.67 [95% CI] −0.89, −0.45; p < 0.001 ), and symptoms of depression (−0.40 [95% CI] −0.55, −0.24; p < 0.001 ) and that it improves both components of health-related quality of life (physical: 0.77 [95% CI] 0.47; 1.08; p < 0.001 ; mental: 0.49 [95% CI] 0.27; 0.71; p < 0.001 ). Conclusions . This study concludes that aerobic and muscle strengthening exercises are the most effective way of reducing pain and improving global well-being in people with fibromyalgia and that stretching and aerobic exercises increase health-related quality of life. In addition, combined exercise produces the biggest beneficial effect on symptoms of depression.